2008
DOI: 10.1177/0143624407087261
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in predicting the impact of climate change on thermal performance of domestic buildings in the UK

Abstract: Buildings typically have a long life span, which can easily reach 50 or 100 years. In the light of expected climate change it is therefore important to look towards the future, and to analyse how buildings will cope with the changes in climate that are predicted by the climatologists. In such long-term predictions of building performance, uncertainties play a large role. This paper describes a preliminary study that aims to better map out the consequences of dealing with a whole range of uncertainties in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…The input parameter values were chosen carefully to make the simulation as realistically pessimistic as possible for typical dwellings and typical occupant behaviour but also to generate useful, interpretable results and therefore some compromises were made within the capabilities of the software. Research by de Wilde et al 8 has shown that although great uncertainty is involved in determining domestic energy demand, household energy use displays a normal distribution within approximately a 11-35 GJ/year total household energy consumption range, for the UK. Therefore to calculate a nationwide future scenario, a typical household demand for electricity and gas must be established whilst also identifying sensitivity ranges for key inputs.…”
Section: Methodsmentioning
confidence: 99%
“…The input parameter values were chosen carefully to make the simulation as realistically pessimistic as possible for typical dwellings and typical occupant behaviour but also to generate useful, interpretable results and therefore some compromises were made within the capabilities of the software. Research by de Wilde et al 8 has shown that although great uncertainty is involved in determining domestic energy demand, household energy use displays a normal distribution within approximately a 11-35 GJ/year total household energy consumption range, for the UK. Therefore to calculate a nationwide future scenario, a typical household demand for electricity and gas must be established whilst also identifying sensitivity ranges for key inputs.…”
Section: Methodsmentioning
confidence: 99%
“…In order to achieve this, three options were considered. The first was to use a weather file from a European location such as Rome [24] or Milan [25] to approximate the South East England climate later this century. However, the different latitudes of these locations would affect solar shading calculations.…”
Section: Weather Datamentioning
confidence: 99%
“…Some of the previous research identified has used climate data from warmer locations outside the UK, such as Rome [20] and Milan [21]. This allows the use of real weather files in the simulations, which are thought to approximate future climate conditions for the UK, assuming a medium high emissions scenario.…”
Section: Weather Datamentioning
confidence: 99%